Predicting human elephant conflict - Chris Thouless (Pachyderm)
Reviews the establishment of AfESG's Human-Elephant Conflict Task Force (HETF) and its initial concerns and approaches to the problem. Looks at problems of predicting potential elephant-human conflict in nonagricultural as well as agricultural areas and suggests assessing maps using overlap between elephant range (excludng protected areas) and high densities of human population would be useful.